Evaluasi Program Pembelajaran Berbasis Proyek Pada Mata Pelajaran IPA Di SMP IT At Taqwa Surabaya - Inkana Fira Nur Rahma; Nur Azizah; Putri Sa’adah; Prasintha Mia Yulanda Putri (Pusat Riset dan Inovasi Nasional, 2023)
Islamic Junior High School At-Taqwa Surabaya. The research method used is an interview with the Vice Principal for curriculum, and science subject teachers which focuses on the implementation and impact of project-based learning programs on student learning outcomes, student involvement, and innovations made by science subject teachers. The results showed that the project-based learning program at At Taqwa Surabaya Integrated Islamic Junior High School succeeded in arousing students' interest and involvement in the learning process. This program also has a positive impact on students' learning achievement by increasing the value of their skills and understanding through science lessons. Science teachers respond positively to this innovation and feel that project-based learning provides better opportunities for students to develop creativity, problem-solving skills and teamwork, so it can be used as a guideline for other schools that want to develop their learning through project-based learning in their curriculum